2012
DOI: 10.1037/a0027753
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and effects of life event exposure among undergraduate and community college students.

Abstract: The purposes of this study were to assess lifetime and recent exposure to various life events among undergraduate and community college students and to assess the relation between event exposure and a broad range of outcomes (i.e., mental and physical health, life satisfaction, grade point average). Undergraduate students from a midwestern university (N = 842) and a community college (N = 242) completed online measures of lifetime event exposure and outcomes at Time 1 and recent event exposure at Time 2 two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 30 publications
(44 reference statements)
9
86
2
Order By: Relevance
“…These findings are consistent with past research indicating that college women report greater levels of stress than their male peers, 31 and that the number of ALEs experienced is positively associated with poor outcomes. 1 In addition, time since a stressful ALE has also been found to be negatively associated with anxiety 33 and grief 8 for college students.…”
Section: Resultsmentioning
confidence: 97%
“…These findings are consistent with past research indicating that college women report greater levels of stress than their male peers, 31 and that the number of ALEs experienced is positively associated with poor outcomes. 1 In addition, time since a stressful ALE has also been found to be negatively associated with anxiety 33 and grief 8 for college students.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, up to 79% of college students may be exposed to at least one experience of psychological abuse, 31% to at least one incident of physical abuse, and 36% to at least one incident of sexual abuse in an intimate relationship (Avant, Swopes, Davis, & Elhai, 2011). Higher levels of cumulative trauma are associated with greater rates of negative personal/emotional adjustment in college students (Banyard & Cantor, 2004); trauma and other negative event exposures put undergraduate students at greater risk of developing posttraumatic stress, depression, substance use disorders, and other psychological problems (Anders et al, 2012;Read et al, 2011;Turner & Butler, 2003).…”
Section: The Trauma-informed Perspectivementioning
confidence: 97%
“…According to Frazier and colleagues' (2009) study, lifetime exposures to sexual assault, unwanted sexual attention, and family violence are associated with the highest levels of distress among undergraduates. Non-Criterion A1 traumas, such as unsupportive or hurtful interpersonal events, have also been related to negative student outcomes, including increased PTSD symptoms, other distress, and poorer physical health (Anders, Frazier, & Shallcross, 2012).…”
Section: The Trauma-informed Perspectivementioning
confidence: 98%
See 1 more Smart Citation
“…Negative life events are events that "can lead to maladjustment and disturbances that most likely to result in readjustment-requiring changes in one's daily life" (Holmes and Rahe, 1967). Anders et al (2012) investigated 1084 undergraduate and community college students and found that students who experienced more life events reported poorer outcomes in a range areas of school adjustment, including lower grade point average, more distress and lower life satisfaction. A survey conducted by Reyes-Rodríguez et al (2013) found that negative life events increased the prevalence of depression symptoms and its severity among freshmen college students, which were regarded as one of important emotional maladjustment during school life.…”
Section: Introductionmentioning
confidence: 99%